Building User‐Readiness for Satellite Earth Observing Missions: The Case of the Surface Water and Ocean Topography (SWOT) Mission. Issue 6 (29th October 2022) - Hossain, Faisal; Das, Pritam; Srinivasan, Margaret; Tsontos, Vardis; Oaida, Catalina M.; Nickles, Cassandra; McNelis, Jack; Bonnema, Matthew; Picot, Nicolas; Peña‐Luque, Santiago; Doorn, Bradley; Vinogradova‐Shiffer, Nadya; et al.
Abstract: The goal in this commentary is to share the development of the NASA Applied Science pre‐launch protocol called the Early Adopter Program (EAP) that is designed to build user‐readiness of planned satellite Earth observing missions proactively and before the launch . Here we focus in particular on the Surface Water and Ocean Topography satellite mission EAP as an illustration of benefits of such a program of proactive and sustained user community engagement. Such a commentary will be of value to other satellite Earth observation missions that are currently in service, scheduled for launch or prioritized for development in the near future. Plain Language Summary: The commentary sheds light on the many years of preparation for a planned satellite mission for surface water (Surface Water and Ocean Topography mission) to make the data as user‐ready as possible. We believe such a commentary may be of interest to other communities involved in planning, operation or use of other satellite missions. Key Points: Planned satellite earth missions today require proactive engagement with a broad user community The Surface Water and Ocean Topography Early Adopter program represents the start of what is possible through sustained engagement with stakeholder community Such early engagement is a template for other planned satellite Earth missions to maximize the return on public investments in such missions